2016
DOI: 10.1016/j.ijheatmasstransfer.2016.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Thermal rectifier efficiency of various bulk–nanoporous silicon devices

Abstract: Our objective is to calculate and to compare the rectifying thermal coefficient of various bulkporous silicon configurations. We consider successively homogeneous devices involving twoand three elements and several graded devices characterized by variable porosity and/or size of the pores along the system. The criterion is to obtain rectifying coefficients different from one in order that thermal rectification be as efficient as possible. In that respect, it turns out that the porous-bulk-porous configurations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…2). Note that studies also suggest that a non-linear temperature gradient can lead to rectification [16,21], in our case, however, it is the variation of the phonon MFPs that does so. Another important observation is the monotonic decrease in rectification as the pore columns pile up across the simulation domain, in the transport direction, in which case the structure becomes more and more 'symmetric'.…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…2). Note that studies also suggest that a non-linear temperature gradient can lead to rectification [16,21], in our case, however, it is the variation of the phonon MFPs that does so. Another important observation is the monotonic decrease in rectification as the pore columns pile up across the simulation domain, in the transport direction, in which case the structure becomes more and more 'symmetric'.…”
Section: Resultsmentioning
confidence: 41%
“…Recently, significant research has been done on understanding and controlling phonon transport in nanostructures for novel materials and applications [1][2][3][4][5][6][7][8]. Since initial findings of thermal rectification between Cu and Cu2O [9] interfaces in the 1930s, various experimental [10][11][12] and theoretical [13][14][15][16][17][18][19][20][21] studies have investigated thermal rectification in different materials. Rectification values of up to 350% were theoretically predicted in graphene nanoribbons [22], while experiments showed that graphene junctions could provide even higher values of up to 800% rectification [12].…”
Section: Introductionmentioning
confidence: 99%
“…where R K is the Kapitza resistance [20][21][22]. If the graded material is in contact with a liquid, a convection term should be added to the left-hand side in Equation (5).…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…The unusual behavior of thermal diodes have paved the way for controlling the rate of heat flows in a similar way as is done with their electric current counterparts in modern electronic devices. Over the last few years, the rectification effect has been theoretically studied through thermal diodes driven by electrons [5], photons [6,7,8,9,10], phonons [3,4,11,12,13], [17,18], quantum dots, hybrid quantum structures [14,15,16], and nanoporous silicon devices [17]. The experimental study of the diode effect, on the other hand, was done by using quantum dots [19], carbon nanotubes structures [20], graphene nanoribbons [21], nanoporous graphene [22], solid-liquid phase change thermal diodes [23], as well as electrostatic [24] and bulk oxide materials [25].…”
Section: Introductionmentioning
confidence: 99%